Antibiotic-resistance gene transfer in antibiotic-resistance bacteria under different light irradiation: Implications from oxidative stress and gene expression. (1st February 2019) - Chen, Xiaofang; Yin, Hongliang; Li, Guiying; Wang, Wanjun; Wong, Po Keung; Zhao, Huijun; An, Taicheng
Abstract: Due to the significant public health risks, there is substantial scientific interest in the increasing abundance of antibiotic-resistance bacteria (ARB) and the spread of antibiotic-resistance genes (ARGs) in aquatic environments. To clearly understand the mechanism of ARG transfer, this study examined the conjugative transfer of genes encoding resistance to cephalosporin ( b l a C T X ) and polymyxin ( mcr-1 ) from two antibiotic-resistant donor strains, namely E. coli DH5α (CTX) and E. coli DH5α (MCR), and to a streptomycin-resistant receptor strain ( E. coli C600 (Sm)). Conjugative transfer was specifically studied under different light irradiation conditions including visible light (VL), simulated sunlight (SS) and ultraviolet light (UV254nm ). Results show that the conjugative transfer frequency was not affected by VL irradiation, while it was slightly improved (2–10 fold) by SS irradiation and extremely accelerated (up to 100 fold) by UV irradiation. Furthermore, this study also explored the link between ARG transfer and stress conditions. This was done by studying physiological and biochemical changes; oxidative stress response; and functional gene expression of co-cultured AR- E. coli strains under stress conditions. When correlated with the transfer frequency results, we found that VL irradiation did not affect the physiological and biochemical characteristics of the bacteria, or induce oxidative stress and gene expression. For SS irradiation, oxidative stress occurred slowly, with a slight increase in the expression of target genes in the bacterial cells. In contrast, UV irradiation, rapidly inactivated the bacteria, the degree of oxidative stress was very severe and the expression of the target genes was markedly up-regulated. Our study could provide new insight into the underlying mechanisms and links between accelerated conjugative transfer and oxidative stress, as well as the altered expression of genes relevant to conjugation and other stress responses in bacterial cells. Graphical abstract: Image 1 Highlights: The transfer frequency of b l a C T X and mcr-1 genes was not affected by VL irradiation. Simulated sunlight and especially UV radiation stimulate ARG conjugative transfer. The conjugative transfer links with bacterial oxidative stress and gene expression. The conjugative transfer frequency was positive related to bacterial stress response.